Climate, peace and security programming in the Arab States: Considerations for integrated programming in Jordan, Yemen, Iraq and Somalia - Schapendonk, Frans John Adrianus; Jaskolski, Martina; McMurray, Spencer; Farook, Omar; Isayan, Nora (2023)
The link between climate change and peace and security is becoming increasingly evident as the world grapples with the consequences of a warming planet. Climate change exacerbates existing inequalities and conflicts, and acts as a catalyst for new ones, as competition for dwindling resources, such as water and land intensify. Rising sea levels and extreme weather events displace communities, straining host communities’ resources, leading to potential social unrest. Additionally, climate-induced food and water scarcity can speak conflict over access to these essential resources. Furthermore, climate change can amplify existing social and economic inequalities, which can contribute to instability and unrest. Understanding the climate, peace, and security linkages, and developing integrated policies and programmes across this nexus, is critical to ensuring global peace and security, and addressing humanitarian needs while supporting sustainable development. This brief - based on the outcomes of a stakeholder workshop held in Cairo in March 2023 - outlines several best practices and lessons learned for the design, implementation, and evaluation of integrated programming that builds resilience to both climate change and security risks.